Peran Guru Dalam Mengatasi Anak Hiperaktif di Sekolah Khusus Negeri - Alwahidah, Nabila Zulfa (Jurnal Pendidikan Kebutuhan Khusus, 2026)
This study aims to describe the role of teachers in managing hyperactive children in a public special needs school and to identify the forms of hyperactive behavior as well as teachers’ responses to these behaviors. A qualitative approach with a case study design was employed. Data were collected through direct classroom observations and in-depth interviews with teachers and parents. Data analysis was conducted inductively using an interactive analysis model involving data reduction, data display, and conclusion drawing carried out simultaneously. The findings indicate that hyperactive children exhibit characteristic behaviors such as difficulty maintaining attention, inability to remain seated, frequent interruptions, and impulsive actions during learning and social interactions. The results also reveal that teachers play a crucial role in addressing these behaviors through emotional approaches, step-by-step instructions, consistent classroom routines, and continuous supervision during learning activities. However, limited understanding and the lack of specialized training related to ADHD remain significant challenges in implementing effective intervention strategies. This study highlights the importance of enhancing teachers’ knowledge and competencies in managing hyperactive children to foster a more supportive and inclusive learning environment.